1991
DOI: 10.1063/1.350268
|View full text |Cite
|
Sign up to set email alerts
|

Preparation of TlCaBaCuO high-T c superconducting thin films on LaAlO3 substrates

Abstract: Pure 2122 phase and 2223 phase superconducting TlCaBaCuO thin films have been reproducibly prepared on (100)LaAlO3 substrates by dc magnetron sputtering using a pair of superconducting Tl2Ca2B2Cu3O10 targets and post-annealing at different temperatures. X-ray diffraction analysis indicates that the films are highly c-axis oriented perpendicular to the film surface for both types of the thin films. The critical transition temperature Tc(R = 0) = 98 K and critical current Jc(77 K)=1.0×105 A/cm2 can be obtained f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1992
1992
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In the present paper, we describe a two-step growth technique [9] that allows us to maintain the chemical composition of the film: PbBi1212 deposited on a SrTiO 3 (STO) substrate at low temperature forms an amorphous film which, at high temperature, crystallizes with the crystallographic symmetry of the substrate. We demonstrated that this technique works well for fabricating single-phase PbBi1212 epitaxial films.…”
Section: Introductionmentioning
confidence: 99%
“…In the present paper, we describe a two-step growth technique [9] that allows us to maintain the chemical composition of the film: PbBi1212 deposited on a SrTiO 3 (STO) substrate at low temperature forms an amorphous film which, at high temperature, crystallizes with the crystallographic symmetry of the substrate. We demonstrated that this technique works well for fabricating single-phase PbBi1212 epitaxial films.…”
Section: Introductionmentioning
confidence: 99%
“…The Pb1212 epitaxial film was grown using a two-step technique [16] in which an amorphous film deposited on a SrTiO 3 (STO) substrate via room-temperature sputtering is annealed in a closed ceramic container prepared using the same material as that of the film. Similar techniques are often used for precise control of the composition of Hg-and Tl-based cuprates [17,18] whose chemical composition is difficult to maintain during the growth due to the high vapor pressures of heavy metal elements. Here, we stress that our two-step technique allows us to obtain Pb1212 with fewer Pb vacancies and lattice strain, which leads to an increase in T c .…”
Section: Introductionmentioning
confidence: 99%